Dynamic P2P trust model based on context factors - Yi-chun LIU; Ying-hong LIANG (Tongxin xuebao)
A multi-dimensional trust model was constructed based on the context factors.The direct trust of the interac-tive entities was estimated by integrating the time-decay factor,the transaction impact factor and the participation fre-quency.The trust similarity algorithm was designed based on the Dice similarity and the feedback credibility was aggre-gated from multiple trust chains.The direct interaction,the evaluation similarity and the trust chain was integrated for calculating the recommendation trust.The peer's trust was evaluated by combing the direct trust and the recommendation trust.A new mechanisam was proposed for the trust's update,incentive or punishment according to the peer's behavior on the interaction.The practical example analysis shows that the proposed model can effectively explain the effect of the transaction contextual factors on the entity trust,and can improve the trust sensitivity to the context transaction factors.